A Combined Radial and Pedal Access to Treat a Flush Chronic Total Occlusion of the Superficial Femoral Artery in a Critical Limb Ischemia Patient. (March 2019) - Shammas, Nicolas W; Radaideh, Qais
We present a case of a flush chronic total occlusion of the superficial femoral artery treated successfully with a combined antegrade approach using radial access and a retrograde approach using a pedal access. Patient has total occlusion of the contralateral left external iliac and common femoral artery. Our case illustrates the feasibility of the combined pedal-radial approach in treating flush occlusions of the superficial femoral artery.